Local Delivery of PHD2 siRNA from ROS‐Degradable Scaffolds to Promote Diabetic Wound Healing. Issue 21 (26th September 2016) - Martin, John R.; Nelson, Christopher E.; Gupta, Mukesh K.; Yu, Fang; Sarett, Samantha M.; Hocking, Kyle M.; Pollins, Alonda C.; Nanney, Lillian B.; Davidson, Jeffrey M.; Guelcher, Scott A.; Duvall, Craig L.
Abstract : Small interfering RNA (siRNA) delivered from reactive oxygen species‐degradable tissue engineering scaffolds promotes diabetic wound healing in rats. Porous poly(thioketal‐urethane) scaffolds implanted in diabetic wounds locally deliver siRNA that inhibits the expression of prolyl hydroxylase domain protein 2, thereby increasing the expression of progrowth genes and increasing vasculature, proliferating cells, and tissue development in diabetic wounds.